α-Diimine complexes of transition metals for the polymerisation of lower α-olefins - Fullaway, Phillip V. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2005.